The Impact of Economic growth on environmental quality - Paweł Bartoszczuk (Studia Ecologiae et Bioethicae)
With growing interest in the development of environmentally friendly solutions to the world's problems, including the deterioration of the global environment and fluctuating economic conditions, the need for methods to predict the effects of political decisions becomes more urgent. This article examines the possible impact of economic development on environmental quality. Be warned that without significant reductions in throughput at any given time, we can expect a substantial drop in the main divisions of food, energy and industrial production. The model presented in this article should alert decision-makers to the looming problem of economic spikes in a world where resources are beginning to run out.